2020
DOI: 10.1088/1742-6596/1442/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Stock portfolio optimization using priority index and genetic algorithm

Abstract: Stock portfolio is a kind of investment which consists of several stocks. The aim of a stock portfolio is to minimize the risk of an investment and maximize the return on investment. To construct the optimum portfolio of stocks, one needs a strategy of stock selection and must determine the percentage of investment in each stock selected. In this paper, both the priority index method and genetic algorithm are applied to optimize the stock portfolios in terms of the return. Priority index is used in stock selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This feature, combined with the L-Lipschitz continuity of ESG risk-performance functions, allows Bayesian optimization to optimize various ESG criteria with minimal prior knowledge and minimal assumptions about the function's structure, making it a highly adaptable and flexible approach for ESG portfolio management. Prior in the literature, other black-box models -including metaheuristics such as Genetic algorithm (GA) [17] or Simulated Annealing (SA) [18]have also been proposed as alternative portfolio optimization techniques [44][45][46][47][48][49][50][51][52][53]. Bayesian optimization (BO) is a state-of-the-art class of methods that optimize black-boxes.…”
Section: State Of the Art In Portfolio Optimization With Esg And Baye...mentioning
confidence: 99%
“…This feature, combined with the L-Lipschitz continuity of ESG risk-performance functions, allows Bayesian optimization to optimize various ESG criteria with minimal prior knowledge and minimal assumptions about the function's structure, making it a highly adaptable and flexible approach for ESG portfolio management. Prior in the literature, other black-box models -including metaheuristics such as Genetic algorithm (GA) [17] or Simulated Annealing (SA) [18]have also been proposed as alternative portfolio optimization techniques [44][45][46][47][48][49][50][51][52][53]. Bayesian optimization (BO) is a state-of-the-art class of methods that optimize black-boxes.…”
Section: State Of the Art In Portfolio Optimization With Esg And Baye...mentioning
confidence: 99%
“…To determine the exact amount of investment, two objective functions are considered in accordance with equations ( 1) and (2). In relation (1), the goal of maximizing the stock portfolio based on the projected profit (R t(predict) i , i ∈ m) and in relation (2) the goal of minimizing investment risk or in other words minimizing the covariance between the two shares of the company (cov ij , i, j ∈ m). e investment must be made in such a way that in accordance with equation (3) the total volume of transactions does not exceed 1.…”
Section: Random Forestmentioning
confidence: 99%
“…In addition to providing benefits (returns), the investment also has a risk borne by the investor. The higher the rate of return expected by an investor, the higher the risk to be covered by the investor [ 1 ]. The level of risk can be minimized at a certain rate of stock portfolio expectations by forming an appropriate portfolio.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they found that each algorithm showed different advantages over different data sets, and they showed that all these algorithms can be applied for efficient portfolio selection. These techniques have also been used by Moral-Escudero, Ruiz-Torrubiano and Suarez (2006), Chang, Yang and Chang (2009), Özdemir (2011), Eshlaghy, Abdolahi, Moghadasi and Maatofi (2011), Gorgulho, Neves and Horta (2011), Chen, Mabu, and Hirasawa (2011), Woodside-Oriakhi, Lucas, and Beasley (2011, Bermúdez, Segura and Vercher (2012), Pandari, Azar and Shavazi (2012), Ackora-Prah, Gyamerah, Andam and Gyamfi (2014), Hsu (2014), Yakut andÇankal (2016), Zeren andBayğın (2015), Chen, Lin, Zeng, Xu, and Zhang (2017), Jalota and Thakur (2018), Sasaki, Laamrani, Yamashiro, Alehegn and Kamoyedji (2018), Garcia, Guijarro and Oliver (2018), Vasiani, Handari and Hertono (2020.…”
Section: Introductionmentioning
confidence: 99%